ANALISIS USAHATANI PISANG KEPOK DI DESA BANGUN HARJA KECAMATAN SERUYAN HILIR TIMUR KABUPATEN SERUYAN - Muhammad Arief Abdulloh; Jhon Wardie; Berkat A. P. (JOURNAL SOCIO ECONOMICS AGRICULTURAL, 2019)
This study aims: (1) to find out how kepok banana farming performance; and (2) analyzing the income of kepok banana farming in Bangun Harja Village, East Seruyan Hilir Subdistrict, Seruyan District. The research location was chosen purposively with the population of banana farmers in Bangun Harja Village, East Seruyan Hilir Subdistrict, Seruyan District and the samples taken were 66 people using the simple random sampling method. The types of data used in this study include primary and secondary data. The results showed that the characteristics of kepok banana farming in Bangun Harja Village, East Seruyan Hilir Subdistrict, Seruyan District were a) land characteristics, b) kepok banana farming tools, c) production facilities and d) kepok banana production. The calculation results show that the size of the income of kepok banana farming is influenced by the amount of production and production costs. And it is known that the average amount of revenue is Rp.  46,304,734, which is greater than the amount spent, which is Rp. 3,098,969 and the average income received in a year is Rp. 43,110,516. The profit value or R/C Ratio in a year count of 14.9 means that the kepok banana farming in Bangun Harja Village, East Seruyan Hilir Subdistrict, Seruyan District is profitable, because the R/C Ratio value is greater than 1.